The Influence of Intrinsic Motivation and Non-Physical Work Environment on Police Performance: The Mediating Role of Job Satisfaction in Densus 88 Intelligence Division - Miranda Fisa; Titing Widyastuti (Pustaka Digital Indonesia, 2025)
This study examines the influence of intrinsic motivation and the non-physical work environment on employee performance, with job satisfaction as a mediating variable, in the Product Analyst Sub-Directorate of the Intelligence Directorate, Densus 88 AT Polri. The research highlights the strategic importance of human resources in supporting organizational effectiveness, particularly in high-stakes intelligence operations focused on counterterrorism in Indonesia. A quantitative approach was employed using a saturated sampling technique involving 103 personnel. Data were collected through structured questionnaires using a Likert scale and analyzed using multiple linear regression and path analysis, including the Sobel test to assess mediation. The results reveal that intrinsic motivation (β = 0.28; p = 0.02) and the non-physical work environment (β = 0.29; p = 0.00) significantly and positively affect performance. Furthermore, job satisfaction (β = 0.62; p = 0.00) significantly contributes to performance and fully mediates the relationship between the independent variables and performance (p = 0.00). These findings underscore the importance of enhancing intrinsic motivation and creating a supportive work environment to foster job satisfaction and, in turn, improve performance. The study offers practical implications for organizational leaders in intelligence institutions to consider psychological and social factors in optimizing employee output under pressure-intensive environments.